Multinuclear Diffusion NMR Spectroscopy and DFT Modeling: A Powerful Combination for Unraveling the Mechanism of Phosphoester Bond Hydrolysis Catalyzed by Metal‐Substituted Polyoxometalates. Issue 11 (4th February 2015) - Luong, Thi Kim Nga; Shestakova , Pavletta; Mihaylov, Tzvetan T.; Absillis, Gregory; Pierloot, Kristine; Parac‐Vogt, Tatjana N.
Abstract A detailed reaction mechanism is proposed for the hydrolysis of the phosphoester bonds in the DNA model substrate bis(4‐nitrophenyl) phosphate (BNPP) in the presence of the ZrIV‐substituted Keggin type polyoxometalate (Et2NH2)8[{α‐PW11O39Zr(μ‐OH) (H2O)}2]⋅7 H2O (ZrK 2:2) at pD 6.4. Low‐temperature 31P DOSY spectra at pD 6.4 gave the first experimental evidence for the presence of ZrK 1:1 in fast equilibrium with ZrK 2:2 in purely aqueous solution. Moreover, theoretical calculations identified the ZrK 1:1 form as the potentially active species in solution. The reaction intermediates involved in the hydrolysis were identified by means of 1H/31P NMR studies, including EXSY and DOSY NMR spectroscopy, which were supported by DFT calculations. This experimental/theoretical approach enabled the determination of the structures of four intermediate species in which the starting compound BNPP, nitrophenyl phosphate (NPP), or the end product phosphate (P) is coordinated to ZrK 1:1. In the proposed reaction mechanism, BNPP initially coordinates to ZrK 1:1 in a monodentate fashion, which results in hydrolysis of the first phosphoester bond in BNPP and formation of NPP. EXSY NMR studies showed that the bidentate complex between NPP and ZrK 1:1 is in equilibrium with monobound and free NPP. Subsequently, hydrolysis of NPP results in P, which is in equilibrium with its monobound form.